PROBLEMATIKA PENYANDANG DISABILITAS DALAM PELAKSANAAN BIMBINGAN PERKAWINAN DI KUA KECAMATAN TALANG KABUPATEN TEGAL - Islam, Hamzah nur; udin, ahmad komar; subekhi, Muhammad abdulah (IAIN BONE, 2024)
This article discusses the problem of implementing marriage guidance for people with disabilities at the KUA Talang District, Tegal Regency. At the research location, 5 cases were found from 2003 to 2019. The research approach used was a case study, with data collection techniques using interviews, observation and documentation methods. The data analysis technique uses qualitative descriptive.The results of the research show that the implementation of marriage guidance for prospective brides with disabilities at KUA Talang is largely in accordance with the decision of the Director General of Islamic Community Guidance No. 189 of 2021. Then the obstacle in implementing marriage guidance for prospective brides with disabilities at KUA Talang is the lack of sign language interpreters for deaf people, guidance modules that do not meet the needs of people with disabilities, especially blind people requiring modules with brilliant letters, as well as a lack of infrastructure and implementation of guidance along with marriage sermons that are too short. Also, there is no issuance of marriage guidance certificates.